Metastatic spread of serous ovarian carcinoma to the bilateral breasts: a rare presentation. Issue 11 (24th November 2022) - Musa, Arif; Joiner, Michael; Dzul, Stephen; Miller, Steven Raymond
Abstract : A woman presented with a mass in her right breast. She had previously been treated with carboplatin, paclitaxel and bevacizumab for serous ovarian carcinoma diagnosed 5 years previously and was currently on maintenance olaparib. A right breast mammogram demonstrated periareolar skin thickening and the physical examination revealed an erythematous, non-blanching cutaneous lesion. A punch biopsy revealed high-grade serous carcinoma of ovarian origin, positive for PAX-8, WT-1 and p53. Positron emission tomogram-CT scan showed diffusely increased fluorodeoxyglucose uptake in the right breast. She was treated with external beam radiation therapy to the right breast and regional lymphatics and received 5200 cGy in 20 fractions to the right breast and supraclavicular region with good response. Two weeks after completing radiation therapy, she presented with a new lesion inferior to her left areola, concerning for metastasis to the contralateral breast. Subsequent biopsy of the left breast identified metastatic serous ovarian carcinoma for which she received an additional 5200 cGy in 20 fractions to the breast.